AICCRA Country Scaling Vision: Zambia - Jacobs-Mata, Inga; Dahl, Hauke; Thai, Minh; Mutenje, Munyaradzi; Kakwasha, Keagan; Pele, Winnie; Makungwe, Mirriam; Muzungaire, Lizzy; Mudege, Netsayi N. (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
In this brief, we present AICCRA Zambia's scaling vision. Our scaling strategy employs a number of interconnected and mutually reinforcing channels. These include public and private sector scaling partnerships, individual and collective investments, financing mechanism for SMEs, institutional capacity building and multistakeholder dialogues (Figure 2). AICCRA works with Zambian partners to scale actionable climate smart agriculture (CSA) and climate information services (CIS) innovation bundles that contribute to smallholder farmers’ water and food security and build resilience.